Direct rapid antibiotic susceptibility test (dRAST) for blood culture and its potential usefulness in clinical practice. Issue 3 (March 2018) - Kim, Jeong‐Han; Kim, Taek Soo; Song, Sang Hoon; Choi, Jungil; Han, Sangkwon; Kim, Dong Young; Kwon, Sunghoon; Lee, Eunyoung; Song, Kyoung‐Ho; Choe, Pyeong Gyun; Bang, Ji Hwan; Kim, Eu Suk; et al.
Abstract : Purpose. : The direct rapid antibiotic susceptibility test (dRAST), based on analysing changes in bacterial micro‐colonies under antibiotic conditions, detects antibiotic resistance within 6 h of direct smear examination results. This study aimed to assess the accuracy of dRAST and evaluate its potential usefulness for improving selection of appropriate antibiotic in real clinical practice settings. Methodology. : We evaluated the accuracy of dRAST by comparing the antibiotic treatments that should have been administered based on dRAST results and the broth microdilution (BMD) test and its potential usefulness via simulation. Result. : For 49/52 (94.2 %) patients with Gram‐positive bacteraemia and 66/67 (98.5 %) patients with Gram‐negative bacteraemia, antibiotics indicated by dRAST results were the same as those indicated by the BMD test. Among 34 patients with ineffective and suboptimal treatment, 19 (55.9 %) of patients could have received optimal treatment 1 to 2 days earlier with dRAST results. Among 33 patients given unnecessary broad‐spectrum antibiotics, 1 to 2 days earlier de‐escalation could have been possible for 27 (81.8 %) patients based on dRAST results. Conclusion. : The introduction of dRAST could increase the use of optimal antibiotics and reduce unnecessary broad‐spectrum antibiotic use in the early period of bacteraemia.